Pengembangan Alat Uji Pengaruh Variasi Kelengkungan Impeller 4 Sudu Terhadap Kinerja Pompa Sentrifugal - Khusnul Hasby, Indra Herlamba, Nur Kholis (Reaktom : Rekayasa Keteknikan dan Optimasi, 2021)
Pumps are equipment that functions to move fluid flow from one place to another. In pumps that play an important role is the impeller, now there are many modifications and innovations of pump impellers to support every industrial need. The purpose of this study was to determine the effect of the impeller with variations in blade curvature on the performance of a centrifugal pump using variations in motor rotation and temperature. In this study, the type of impeller used is an impeller with a total of 4 blades using a blade curvature of 60°, 70°, 80°, and 90° with a motor rotation of 1500 rpm, 1800 rpm, 2100 rpm, and temperature variations of 40° C, 50° C and 60° C. The driving motor used is a motor, the pump that will be used is a radial flow centrifugal pump with a suction and discharge pipe size of inch. The results of this research are the highest head on the impeller with variations in blade curvature is 11.36 meters at a rotational speed of 2100 rpm, a capacity of 37 liters per minute at a rotation speed of 2100 rpm, and an efficiency of 13.60% at 2100 rpm. For the highest head temperature variation of 5.35 meters at a temperature of 40° C. From the analysis of pumps with variations in the curvature of the impeller blades, the larger the blade gap on the impeller, the smaller the head, capacity, and efficiency resulting from the related pump.